2-acetyl-3-amino-1-benzofuran - Iskeleli, NO; Kazak, C; Kirilmis, C; Koca, M (Int Union Crystallography, 2005)
The title compound, C10H9NO2, displays the characteristic features of a benzofuran derivative. The molecular structure is nearly planar with an intramolecular N-H center dot center dot center dot O hydrogen bond involving the amino group and the acetyl carbonyl O atom. In the crystal structure, there are intermolecular N-H center dot center dot center dot O and C-H center dot center dot center dot O interactions, which help to stabilize the structure.